Evaluation of concomitant peripheral arthritis in patients with recent onset axial spondyloarthritis: 5-year results from the DESIR cohort - López-Medina, Clementina (Arthritis Res Ther, 2019)
BACKGROUND: (a) To describe the prevalence and incidence of peripheral arthritis during 5 years of follow-up in recent axial spondyloarthritis (axSpA), (b) to evaluate factors associated with their appearance and (c) to assess their impact on treatment, patient-reported outcomes and sick leave after follow-up. METHODS: Data from the early axSpA patients from the DESIR cohort (first 5 years of follow-up) were analysed. Prevalence and incidence of peripheral arthritis at each study visit were calculated. A multivariate analysis was performed to evaluate baseline factors associated with the development of the arthritis. The use of drugs, the impact on patient-reported outcomes and days of sick leave were compared in both groups over time. RESULTS: Out of the 708 patients included in DESIR, 255 (36.0%) showed at least one episode of arthritis (151 before the inclusion visit and 104 during the follow-up), with an incidence of 3.7 cases per 100 person-years. Patients with peripheral arthritis were more likely (OR, 95%CI) to be aged ≥ 33 years (1.60, 1.12–2.27), non-smokers (1.58, 1.10–2.27) and HLAB27 negative (1.47, 1.04–2.08) and have presented with at least one episode of dactylitis (8.50, 4.96–14.60) and enthesitis (2.00, 1.41–2.84). Patients with peripheral arthritis showed a significant greater use of TNFb, csDMARDs and corticosteroids over follow-up; higher levels on BASDAI (40.46 vs. 34.28) and BASFI (27.89 vs. 22.52); poorer quality of life; and higher number of days of sick leave (17.97 vs. 12.78) over time. CONCLUSION: In recent axSpA, 36% of patients reported peripheral arthritis at any time of the disease, being associated with negative HLAB27, non-smokers and with other peripheral manifestations. Patients with arthritis showed a higher burden of disease.